Adiposity indicators, cardiometabolic parameters and critical size of adipocytes in premenopausal women - Srdic Galic, Biljana; Stokic, Edita; Korac, Aleksandra; Udicki, Mirjana; Mandic, Aljosa (Progress in Nutrition, 2022)
Background and aim: Adipocyte hypertrophy is an indicator of adipose tissue dysfunction that precedes the development of obesity comorbidities. The aim of this study was to analyze relationship between adiposity indicators, cardiometabolic parameters and the size of abdominal adipocytes in premenopausal women, and to develop cut-off levels for anthropometric indicators based on the critical size (100 μm) of visceral adipocytes. Methods: Study group consisted of 50 premenopausal women aged 42.88±7.17y. Subcutaneous and visceral (omental) adipose tissue samples were taken during laparotomy, and adipocyte size was analysed. Prior surgery all subjects underwent body composition analysis, anthropometric mesurements, and cardiometabolic risk assessment. Results: The size of subcutaneous and visceral adipocytes correlated significantly with all indicators of overall and regional adiposity, except thigh skinfold thickness, proximal and distal thigh circumferences. Indicators of upper body adiposity had better correlation with the size of visceral adipocytes comparing to subcutaneous adipocytes. Blood pressure and leptin levels had stronger correlation with the size of subcutaneous, while tryglicerides, HDL-cholesterol, uric acid, glycaemia and HOMA showed better correlation with the size of visceral adipocytes. After adjustment for overall and regional adiposity significant correlation only remained between subcutaneous adipocyte size and diastolic blood pressure (r=352, p